Development and use of mill scale briquettes in BOF. (7th February 2017) - Kumar, D. S.; Sah, R.; Sekhar, V. R.; Vishwanath, S. C.
Abstract : Generation of high iron containing wastes such as mill scale, dust and sludge are inevitable in steel making process. It is important to develop and implement processes to recycle and re-use these wastes. An attractive option is to recycle these wastes through BOF steel making process, but is not suitable for handling and efficient operation in available forms. Present work shows the briquetting of steel making wastes using various binders in a pilot scale briquetting machine. In briquetting tests, the effecting parameters have been studied for determining the best combination of binders and operating parameters. A process for briquetting mill scale in optimum combination with CRM dust and BOF dusts using an organic binder has been established. Separate indices were formulated as acceptance criterion for use of mill scale briquettes in BOF service conditions involving dynamic, crushing, abrasive and thermal loads. Subsequently, series of trials were conducted with use of mill scale briquettes as secondary coolant replacing iron ore in 130T LD converter. The present paper compares the effect of mill scale briquettes vis-à-vis iron ore on process parameters in BOF steel making and also highlights its operational advantages.